Exploration of the PET‐RAFT Initiation Mechanism for Two Commonly Used Photocatalysts. Issue 11 (13th February 2019) - Corrigan, Nathaniel; Xu, Jiangtao; Boyer, Cyrille; Allonas, Xavier
Abstract: An investigation into the PET‐RAFT initiation mechanism (photoinduced electron/energy transfer‐reversible addition‐fragmentation chain transfer) for two frequently used photocatalysts with five RAFT agents has been conducted through analysis of electron transfer and triplet energy transfer (electron exchange) pathways. The electronic and redox properties of the studied RAFT agents were determined through quantum mechanical calculations and cyclic voltammetry measurements, respectively. Gibbs free energy changes for both electron transfer and electron exchange mechanisms were then calculated and compared to quenching rate constants determined by laser flash photolysis (LFP). Transient absorption spectra for the photocatalyst‐RAFT agent combinations were also measured by LFP to substantiate the energetics considerations, which show that triplet energy transfer through a Dexter electron exchange mechanism for the activation of RAFT agents is probable. The experimental data has been fitted by Balzani's energy transfer model which provides support for a Dexter electron exchange mechanism in these systems. Abstract : A bundle of energy : The initiation mechanism for PET‐RAFT polymerization using the transition metal photocatalysts Ru(bpy)3 2+ and Ir(ppy)3 was investigated through a combined computational and experimental study. An energy transfer (Dexter electron exchange) rather than an electron transfer mechanism is probable for the investigated systems.